PEMBUATAN BUBUK CABAI MERAH (BUCAMER) UNTUK MENGOPTIMALKAN PRODUKSI DAN PEMASARAN CABAI DI KOTA PAGAR ALAM - Inda Anggraini; Dedi Setiadi; Anggia Martiana (Fakultas Pertanian, 2025)
This Community Partnership Program (PKM) activity aims to increase the capacity of farmer groups in processing red chilies into value-added products as an effort to overcome fluctuations in the price of fresh chilies in Pagar Alam City. The activity partner is the Sukamaju Farmer Group in Lubuk Buntak Village/Subdistrict, which faces major problems in the form of limited post-harvest processing skills, poor packaging quality, and suboptimal agricultural product marketing strategies. To address these issues, the PKM team provided solutions in the form of training on making red chili powder (BuCaMer), applying appropriate technology (drying equipment, grinders, and sealers), assistance with product packaging and label design, and training on digital marketing through social media and marketplaces. The implementation methods included field observations, demonstration-based training, intensive assistance, and evaluation through pre-tests 2,6 and post-tests 4,02. The results of the activities showed a significant improvement in the partners' skills in the production, packaging, and marketing of products. BuCaMer products were successfully produced with improved hygiene smooth texture, and longer shelf life. Product packaging became more attractive and informative, while the digital marketing capabilities of farmer group members improved through the practice of using social media as a promotional tool. Pretest and posttest evaluations showed a ±40% increase in participants' knowledge, confirming the effectiveness of the program.